2020
DOI: 10.1038/s41587-019-0390-x
|View full text |Cite
|
Sign up to set email alerts
|

Peptide–TLR-7/8a conjugate vaccines chemically programmed for nanoparticle self-assembly enhance CD8 T-cell immunity to tumor antigens

Abstract: Personalized cancer vaccines (PCVs) targeting patient-specific neoantigens are a promising cancer treatment modality; however, neoantigen physicochemical variability can present challenges to manufacturing PCVs in an optimal format for inducing anticancer T cells. Here, we developed a vaccine platform ("SNP-7/8a") based on charge-modified peptide-TLR-7/8a conjugates that are chemically programmed to self-assemble into nanoparticles of uniform size (~20 nm) irrespective of the peptide antigen composition. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
239
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 259 publications
(241 citation statements)
references
References 70 publications
1
239
1
Order By: Relevance
“…Different clinical trials with peptide vaccines have shown the efficacy of adjuvants like Montanide and Freud's adjuvant (61)(62)(63). Also addition of Addavax and poly I:C or other TLR ligands like CpG to peptide vaccines has shown good efficacy in pre-clinical models (64)(65)(66)(67). Furthermore, the role of αGC as adjuvanting component has been extensively described in multiple studies (68)(69)(70)(71)(72).…”
Section: Discussionmentioning
confidence: 99%
“…Different clinical trials with peptide vaccines have shown the efficacy of adjuvants like Montanide and Freud's adjuvant (61)(62)(63). Also addition of Addavax and poly I:C or other TLR ligands like CpG to peptide vaccines has shown good efficacy in pre-clinical models (64)(65)(66)(67). Furthermore, the role of αGC as adjuvanting component has been extensively described in multiple studies (68)(69)(70)(71)(72).…”
Section: Discussionmentioning
confidence: 99%
“…This ensures that the same APC that take up antigen receive additional danger signals and thus are competent to provide costimulatory signals to T cells. This approach has been successful in animal models that conjugate long peptides to a TLR agonists 81‐83 . Peptides can also be expressed as fusions with proteins that direct them towards antigen processing machinery and HLA presentation 84 .…”
Section: Vaccine Designmentioning
confidence: 99%
“…The free polymer chains conjugated with imidazoquinoline were liberated, which triggered the TLR7/8 pathway [ 30 ]. Furthermore, nanomedicines incorporating both adjuvants and tumor antigens have also been exploited as cancer vaccines to mount an adaptive immune response against overexpressed self-antigens or neo-antigens that arise from somatic mutations in the tumor [ 31 ]. In addition to synthetic materials, cell-derived nanocarriers have shown their potential in delivering antigens for immunotherapy.…”
Section: Opportunities Of Nanomedicine In Immunotherapymentioning
confidence: 99%